Design & Usabilità in ambito sanitario Il progetto dei dispositivi medici - Pistolesi, Mattia (Serie di architettura e design, 2020)
The progressive ageing of the global population is on the one hand a goal of today's society, and at the same time one of the main socio-economic problems of health and pension systems. The transition from hospitalization to home treatment seems to be a first concrete response. The main reasons that push towards the strengthening of home care are also favoured by new technologies applied to health care that aim to contain public spending, through the implementation of innovative services, including medical devices to use at home. At the same time, the increase in risk conditions caused by the complexity of hospital care requires greater attention and immediate intervention, as represented by a study conducted by two researchers at John Hopkins University, who have shown that medical errors are the third leading cause of mortality in America. This volume is addressed to designers, students of Design courses and all those who address the disciplines of the project. To give them a better understanding of the theoretical-practical course described in the book, this has been divided into two parts. The first part, theory, is dedicated to the description of the current scenario in its multiple aspects - diverging phase -, aimed at defining two design strategies that can be used during the development process of a medical product, both for hospital and home use - converging phase -, as described in the second part, dedicated to practice and experimentation.